Could a global "wicked problems agency" incentivize data sharing? - Susan Ariel Aaronson (Centre for International Governance Innovation (CIGI), 2023)
Global data sharing could help solve "wicked" problems (problems such as climate change, terrorism and global poverty that no one knows how to solve without creating further problems). There is no one or best way to address wicked problems because they have many different causes and manifest in different contexts. By mixing vast troves of data, policy makers and researchers may find new insights and strategies to address these complex problems. National and international government agencies and large corporations generally control the use of such data, and the world has made little progress in encouraging cross-sectoral and international data sharing. This paper proposes a new international cloud-based organization, the "Wicked Problems Agency," to catalyze both data sharing and data analysis in the interest of mitigating wicked problems. This organization would work to prod societal entities - firms, individuals, civil society groups and governments - to share and analyze various types of data. The Wicked Problems Agency could provide a practical example of how data sharing can yield both economic and public good benefits.
Keywords: 330